MATEC Web of Conferences - Zatonov, I. A. specialist in the field of electronics Electronic engineer, assistant of the Tomsk Polytechnic University 1995- (EDP Sciences, 2018)
The article considers the calibration system computation with the inhomogeneity of magnetic field less than 0.1 %. Method of calculation is described. The numerical simulation using finite-element analyze was made for such system as: Helmholtz coils, improved Helmholtz coils, four and six coils system. Authors made the calculation of the magnetic field homogeneity toward axial direction. Based on procure results, authors analyzed magnetic field homogeneity and compared different types of coil systems.